Automation through variable control of a hydroponic cultivation operation - Zambrano Cortés, Nelson Humberto; Behrentz Pfalz, Mery Catherine (Revista Colombiana de Investigaciones Agroindustriales, 2014)
Hydroponics have been one of the agricultural production methods that have developed the most in the recent years, since it has permitted the physical space usage optimization, leaving behind the usage of soil as the base for growth of vegetal species, as well as increasing nutrient and organic fertilizer uptake in favor of its consumption by the plant. On the other hand, the greenhouse-sheltered operations have benefited the producer since it protects the plantation from climate variations, production control and surveillance, and easier, more simple plague control measures are to be taken, depending on the species, although it limits production since it requires a significant physical infrastructure necessary for its implementation. It is well used in the Colombian flower and vegetable production sector. When you fuse these two objects with automation, we find an opportunity to work with a project that has positive agricultural and social impact, developing technology that favors the farmers and their community. We seek the controlled production of high quality food, that offers physical and chemical properties that are favorable for human consumption. Starting from a document base that has been extracted from the advances achieved in some agriculture producing countries, companies that have established operations in this country and low energy consumption technology usage destined to the control of environmental variables, while integrating the School of Aquaculture and Environment ECAPMA, and the School of Basic Sciences, Technology and Engineering ECBTI, that belongs to the CCAV of the city of Zipaquirá, a project is being gestated that integrates agriculture and technology, bringing solutions to real situations through research and implementation of automated systems that allow the control of physiochemical properties in an indoor greenhouse, that provides the ideal conditions for the production of vegetal species. This document compiles the experiences recorded by the Agrónica & Energias Limpias seedbank, and the results obtained during the course of the project, along with the design processes and the further upgrades with the intention of optimizing the greenhouse to the point of maximum yield. Para citar este artículo Zambrano, N. y Behrentz, M. (2014). Automatización de un cultivo hidropónico para el control de variables. Revista colombiana de investigaciones agroindustriales, 1(1), 44-54. DOI: http://dx.doi.org/10.23850/24220582.114